Can we learn from the Mid-Staffordshire Inquiry or is it always someone else's problem? - While, Alison (London J Prim Care (Abingdon), 2015)
KEY MESSAGES: Every healthcare practitioner has a responsibility to put the well-being of patients first. Every healthcare practitioner has a responsibility in the maintenance of healthcare quality and each must take appropriate actions when alerted to poor standards. You cannot assume others will follow up patient concerns and take appropriate actions – the ‘buck’ stops with every practitioner on a professional register. WHY THIS MATTERS TO ME: The regrettable events at Stafford Hospital were avoidable and reading the inquiry report highlighted the extent to which the NHS, and those within it, neglected their duties of care. I was particularly ashamed of my Registered Nurse colleagues who appear to have forgotten that registration as a nurse requires attitudes and behaviours commensurate with the public trust that is attributed to their role. The shocking truth that emerges from the Francis Report(1) is that no organisation or profession emerges with any credit whatsoever – the Deanery, universities, general practitioners (GPs), the General Medical Council (GMC), the Nursing and Midwifery Council (NMC), Monitor…. It is clear that any number of healthcare professionals could have challenged what was happening and alerted the relevant regulatory and supervisory organisations. Those organisations could have then discharged their ‘duties’ rather than taking a benevolent and optimistic view of the emerging evidence and leaving it to others to act.